Temporal Trends of Non-alcoholic Fatty Liver Disease-related Hepatocellular Carcinoma in the Veteran Affairs Population - Mittal, Sahil (Clin Gastroenterol Hepatol, 2014)
BACKGROUND & AIMS: Non-alcoholic fatty liver disease (NAFLD) is a risk factor for hepatocellular carcinoma (HCC). However, no systemic studies from the United States have examined temporal trends, HCC surveillance practices, and outcomes of NAFLD-related HCC. METHODS: We identified a national cohort of 1500 patients who developed HCC from 2005 through 2010 from Veterans Administration (VA) hospitals. We reviewed patients’ full VA medical records; NAFLD was diagnosed based on histologic evidence for, or the presence of, metabolic syndrome in the absence of hepatitis C virus (HCV) infection, hepatitis B, or alcoholic liver disease. We compared annual prevalence values for the main risk factors (NAFLD, alcohol abuse, HCV), as well HCC surveillance and outcomes, among HCC patients. RESULTS: NAFLD was the underlying risk factor for HCC in 120 patients (8.0%); the annual proportion of NAFLD-related HCC remained relatively stable (7.5%–12.0%). In contrast, the proportion of HCC cases associated with HCV increased from 61.0% in 2005 (95% confidence interval, 53.1%–68.9%) to 74.9% in 2010 (95% confidence interval, 69.0%–80.7%). The proportion of HCC cases associated with only alcohol abuse decreased from 21.9% in 2005 to 15.7% in 2010, and the annual proportion of HCC cases associated with hepatitis B remained relatively stable (1.4%–3.5%). A significantly lower proportion of patients with NAFLD-related HCC had cirrhosis (58.3%) compared to patients with alcohol- or HCV-related HCC (72.4% and 85.6%, respectively; P<.05). A significantly higher percentage of patients with NAFLD-related HCC did not receive HCC surveillance in the 3 years before their HCC diagnosis, compared to patients with alcohol- or HCV-associated HCC. A lower proportion of patients with NAFLD-related HCC received HCC-specific treatment (61.5%) than of patients with HCV-related HCC (77.5%; P<.01). However, 1-year survival did not differ among patients with HCC related to different risk factors. CONCLUSIONS: NAFLD is the third most common risk factor for HCC in the VA. The proportion of NAFLD-related HCC was relatively stable from 2005 through 2010. Although patients with NAFLD-related HCC receive less HCC surveillance and treatment, a similar proportion survive for 1 year, compared to patients with alcohol- or HCV-related HCC.